2015
DOI: 10.1063/1.4913948
|View full text |Cite
|
Sign up to set email alerts
|

Effects of polymethylmethacrylate-transfer residues on the growth of organic semiconductor molecules on chemical vapor deposited graphene

Abstract: Scalably grown and transferred graphene is a highly promising material for organic electronic applications, but controlled interfacing of graphene thereby remains a key challenge. Here, we study the growth characteristics of the important organic semiconductor molecule para-hexaphenyl (6P) on chemical vapor deposited graphene that has been transferred with polymethylmethacrylate (PMMA) onto oxidized Si wafer supports. A particular focus is on the influence of PMMA residual contamination, which we systematicall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
65
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(69 citation statements)
references
References 63 publications
4
65
0
Order By: Relevance
“…However, the island sizes are smaller due to the effects of the residue from the transfer process (see Section 7, Supporting Information), which is known to infl uence the growth of OSC structures on graphene. [ 32 ] Figure 3 b shows a low-dose (see Section 8, Supporting Information, for details of low-dose procedures), selected-area electron diffraction pattern from the island highlighted in white in Figure 3 a. The pattern shows sharp diffraction spots that are indicative of crystalline VOPc and are consistent with the molecules being ordered close to the [132] direction relative to the graphene surface, as previously suggested by the XRD measurements.…”
Section: Determination Of Molecular Crystallographysupporting
confidence: 52%
See 1 more Smart Citation
“…However, the island sizes are smaller due to the effects of the residue from the transfer process (see Section 7, Supporting Information), which is known to infl uence the growth of OSC structures on graphene. [ 32 ] Figure 3 b shows a low-dose (see Section 8, Supporting Information, for details of low-dose procedures), selected-area electron diffraction pattern from the island highlighted in white in Figure 3 a. The pattern shows sharp diffraction spots that are indicative of crystalline VOPc and are consistent with the molecules being ordered close to the [132] direction relative to the graphene surface, as previously suggested by the XRD measurements.…”
Section: Determination Of Molecular Crystallographysupporting
confidence: 52%
“…[ 27 ] Understanding how OSCs interact with graphene will be critical for further incorporation, and much work has been done on the graphene/OSC interface. [28][29][30][31][32][33] Recent work has shown how van der Waals epitaxy can result in the growth of large, highly crystalline OSC domains on graphene with improved device performance. [ 30,31 ] This epitaxial growth requires suffi cient interaction between graphene and the molecule, and hence is limited to a subset of OSCs.…”
Section: Introductionmentioning
confidence: 99%
“…16 More specifically, we found that graphene with polymer residues from the transfer process produces a lower packing density molecular layer than that of graphene that has been annealed to remove these residues, similar to what has been described by other groups. 17,18 In this communication,…”
mentioning
confidence: 99%
“…This challenge is particularly highlighted by the many proposed (opto-)electronic graphene devices, starting with simple gated graphene field effect device structures, for which the graphene performance is found to be highly sensitive to the presence of any contaminants [16][17][18][19]. Most polymer [20][21][22][23][24] and metal [25,26] layers used as temporary mechanical supports during graphene transfer have been shown to leave residues on graphene after removal, degrading its electronic properties [12,27,28]. Other common contaminants include lithographic resists, organic solvents, etching products and ambient air [29], all of which can for instance unintentionally dope the graphene (generally p-type [17]) and cause hysteresis in field effect devices [30].…”
Section: Introductionmentioning
confidence: 99%